Hydrogen Peroxide Poisoning—A Rare Cause of Portal Venous Gas - Rohith, Gorrepati; Rajesh, B. S.; Archana, Elangovan; Srinivasan, K. (Indian Journal of Radiology and Imaging, 2021)
Hydrogen peroxide is a clear and odorless liquid at room temperature that can easily be mistaken for water. Its ingestion results in varied clinical and radiological squeals depending on the volume and concentration of the liquid. We present a case of a 22-year-old lady who accidentally ingested 30 to 40 mL of 3% hydrogen peroxide and presented with hematemesis and abdominal pain. On further radiological evaluation, she was found to have portal venous gas and pneumatosis of the bowel wall. She was conservatively managed with 100% oxygen and nil per os for 2 days following which the portal venous gas resolved. Hydrogen peroxide ingestion causes a massive release of oxygen and when its volume exceeds its solubility in blood, gas embolism occurs that is responsible for portal venous gas and pneumatosis. Close monitoring with conservative management will suffice in mild cases without the need for any therapeutic intervention.
Keywords: gas embolism; hydrogen peroxide poisoning; hyperbaric oxygen therapy; portal venous gas